Konservasi Wayang Golek Elung Bandung Koleksi Museum Wayang Kota Tua Jakarta - Rabany, Ramzy; Wardi, I Nyoman; Bawono, Rochtri Agung (Humanis; Vol 24 No 3 (2020), 2020)
Puppet in Indonesia as a world masterpiece has been established by UNESCO on November 7, 2003 in Paris, as a cultural heritage whose conditions for values ??and cultural existence must be preserved. One type of puppets that have been determined is West Java puppet show made from wood. The objectives to be achieved in this study are, concerning the causes of damage and conservation methods that have been carried out by the Jakarta Old Town Puppet Museum in conservation efforts. Data collection techniques in this research are observation, interviews, and literature study. Besides using several theories and data analysis in answering research problems, namely museum management theory and conservation theory, as well as using qualitative analysis, quantitative analysis, material analysis, and physical environment analysis. Bandung Elung puppet show in the Jakarta Old Town Puppet Museum suffered some damage, namely broken joint joint threads, fading colors, fashions appearing, and the loss of the Elung Bandung puppet show. The damage is caused by environmental factors, micro-organisms, and human factors (dissociation). Conservation actions undertaken by the museum in the preservation of wayang golek, namely preventive conservation by cleaning, using silicagels, lighting, temperature and humidity in vitrin / storage media. Curative conservation is carried out by fumigation to kill the activity of micro-organisms in the collection. As for the conservation of restoration, it is done by painting, connecting, gluing and patching which is done by conservators and wayang golek craftsmen.